The impact of education system on economic growth - E. A. Tatarinova (Вестник университета)
The economic growth of a country is influenced by the high level of education. From the point of view of production function, the educational field with various activities can be categorised as a large industry with economic potential because it has significant scientific and human resources. The educational activity in the economic sphere is considered in two directions – the consumer aspect (short-term) and the investment-containing long-term development process. The ongoing educational process actively stimulates the economic growth when the young generation of students acquires modern knowledge, competencies and skills that ensure the future dynamic development of the country. The era of digitalisation has changed the mechanisms of interaction between economic structures, and therefore education should be a driving force of development. Consequently, it is at the origin of new innovative technologies of training. This is necessary to occupy the main positions in the field of scientific and technological progress. Higher education institutions and their activities have become a sector with a leading economic paradigm. The paradigm shift is causal. In order for education not only to exist, but also to be at a decent level, remaining the basis for the development of economic potential and society, it is necessary to make science the base, the foundation of all changes. The principle of “managing education in a business-like, scientific way, without turning it into a business” has become the main one in the context of transforming the educational sector into a modern, innovative sphere, meeting the requirements and needs of the evolving digital time.